Keberadaan Talempong Kayu Di Kenagarian Talang Maur Kecamatan Mungka Kabupaten Lima Puluh Kota - Monna Dini Angraini; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2020)
This study aims to describe the existence of Talempong Kayu in Talang Maur Village, Mungka District, Lima Puluh Kota Regency. This is a qualitative research using a descriptive analysis method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instruments and cameras. The data were collected through literature study, observation, interview, and documentation. The steps of analyzing data are collecting data, describing the data, and making conclusions. The results of this study indicate that Talempong Kayu musical instrument is one of the traditional arts in Talang Village, Mungka District, Lima Puluh Kota Regency. It is played by being hit (idiophone). Talempong Kayu is only used as entertainment for the players, and serves as an emotional expression, aesthetic pleasure, and entertainment. The form of its presentation does not require other people or audiences. In the past, people in TalangMaur village had good enthusiasts and appreciation on Talempong Kayu. However, due to the development of the times, the enthusiasts have decreased considerably. This is due to the fact that today generation replaces their games byandroid phones that can access many games. Furthermore, there has been no government attention in developing Talempong Kayu Art. Talempong Kayu is only played by local people and is not really considered by the government. This is due to the fact that the wood Talempong Art only serves as a substitute musical instrument for training before the metal one, so this is not considered too important for deeper development.